THE ASSOCIATION OF WORK POSTURE AND PSYCHOSOCIAL FACTORS WITH MUSCULOSKELETAL DISORDERS (MSDS) ON EMPLOYEES OF PT PLN UID JAWA TIMUR - Najwa Salsa Nabila; Y. Denny Ardyanto; Deny Nurcahyo Hari Prastya (Departemen K3 FKM Universitas Halu Oleo, 2026)
The era of Industry 4.0 has brought significant changes to the workplace, particularly in the office sector. These changes have increased ergonomic risks that may lead to Occupational Diseases, one of which is Musculoskeletal Disorders (MSDs). Globally, MSDs are among the leading causes of disability in the workplace, accounting for 40–50% of the total costs associated with occupational diseases. This study aims to analyze the association between work posture and psychosocial factors with MSDs. The research was conducted at PT PLN UID Jawa Timur using a quantitative approach with an analytical observational design and a cross-sectional method. The study was carried out in January 2026, involving 59 respondents selected through simple random sampling. Work posture variables were measured through observation using the ROSA method, while psychosocial factors were assessed using the COPSOQ II Short Version questionnaire. The relationship analysis was conducted using the Spearman correlation test with a significant level of 5%. The results showed that work posture (p-value = 0.000) and psychosocial factors (p-value = 0.045) were significantly associated with MSDs. These findings indicate that ergonomic work postures and positive psychosocial conditions can support work effectiveness and improve employee service performance. Therefore, it is recommended that the company implement preventive measures against MSDs through ergonomic education and training, as well as regular management of psychosocial factors to support optimal performance and service quality.